2010
DOI: 10.1524/zkri.2010.1358
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystals: Breaking limitations of data analysis

Abstract: Abstract. A series of "virtual powder diffraction experiments" was made on models of small single crystals and nanocrystals with the core-shell structure. The results of those experiments were elaborated with application of standard methods of data analysis routinely used for reciprocal and real space analyses of polycrystalline materials. It is shown that the assumption of a uniform crystal structure of nano-materials is not justified and, therefore, application of routine procedures of collection and elabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…Table is only valid for micrometer‐sized systems, where Rietveld refinement is applicable. For nanosized particles the Rietveld formalism cannot be used and coherently diffracted waves ( I = ∣ A core + A shell ∣ 2 ) can be treated directly using the Debye formula . The reader is referred to Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table is only valid for micrometer‐sized systems, where Rietveld refinement is applicable. For nanosized particles the Rietveld formalism cannot be used and coherently diffracted waves ( I = ∣ A core + A shell ∣ 2 ) can be treated directly using the Debye formula . The reader is referred to Ref.…”
Section: Resultsmentioning
confidence: 99%
“…For nanosized particles the Rietveld formalism cannot be used and coherently diffracted waves (I = |A core + A shell | 2 ) can be treated directly using the Debye formula. 145 The reader is referred to Ref. [146] for a general treatment of X-ray diffraction from nanoparticles.…”
Section: (1) Macroscopic Functional Propertiesmentioning
confidence: 99%
“…[6,7,33,34] On the other hand, as small nanoparticles show a nonuniform structure, additional extensions to the modelling of nanoparticle structure may be needed to accommodate core/shell structure model. [35,36] This was noted recently on in a study by Palosz et al [36] where they reported the limitations and the perspectives of diffraction studies of the atomic structure of nanoparticles.…”
Section: Introductionmentioning
confidence: 86%
“…values are not available; Gorski & Scherer, 2010;Gotic et al, 2009) is attributed to Fe 3 O 4 NPs. While at the microscale such small variations might be neglected, at the nanoscale they become highly important since they act as possible indicators of surface effects (Palosz et al, 2003(Palosz et al, , 2010Qi & Wang, 2005), as also disclosed by our Debye function analysis (DFA) model on iron oxide NPs. Diehm et al (2012) have recently reviewed this topic and found that, in a nearly systematic manner, small metal oxide NPs tend to slightly expand (typically, but not exclusively, in the 0.1-0.4% range) because of negative surface stress (within the frame of the capillary pressure model).…”
Section: Introductionmentioning
confidence: 84%